Selection of bacterium for mass production of Phasmarhabditis spp. and its effect on the mortality of slugs - Ortmayer, Lukas (Jihočeská univerzita, 2022)
Bacteria was collected from dead slugs and the nematode species Phasmarhabditis apuliae. From the isolated bacteria nine times one bacterium was selected to produce monoxenic nematode/bacteria cultures which then were tested on growth in liquid and solid growth medium and two monoxenic culture were tested on the effectiveness to kill Deroceras species.
Selection of bacterium for mass production of Phasmarhabditis spp. and its effect on the mortality of slugs
Keywords: Biological control; bacteria; slug; parasite; mass cultivation; Phasmarhabditis; nematodes; Biological control; bacteria; slug; parasite; mass cultivation; Phasmarhabditis; nematodes